Implementation of Digital Image processing in Calculating Normal Approach for Spherical Indenter Considering Elastic/Plastic Contact (Journal of Engineering, 2013)
In this work a study and calculation of the normal approach between two bodies, spherical and rough flat surface, had been conducted by the aid of image processing technique. Four kinds of metals of different work hardening index had been used as a surface specimens and by capturing images of resolution of 0.006565 mm/pixel a good estimate of the normal approach may be obtained the compression tests had been done in strength of material laboratory in mechanical engineering department, a Monsanto tensometer had been used to conduct the indentation tests.A light section measuring equipment microscope BK 70x50 was used to calculate the surface parameters of the texture profile like standard deviation of asperity peak heights, centre line average, asperity density and the radius of asperities.A Gaussian distribution of asperity peak height was assumed in calculating the theoretical value of the normal approach in the elastic and plastic regions and where compared with those obtained experimentally to verify the obtained results.